On the analogy between photoluminescence and carrier-type reversal in Bi- and Pb-doped glasses - Hughes Mark A.; Gwilliam Russell M.; Homewood Kevin; Gholipour Behrad; Hewak Daniel W.; Lee Tae-Hoon; Elliott Stephen R.; Suzuki Takenobu; Ohishi Yasutake; Kohoutek Tomáš; Curry Richard J. (Optical Society of America, 2013)
Reaction order in Bi-doped oxide glasses depends on the optical basicity of the glass host. Red and NIR photoluminescence (PL) bands result from Bi2+ and Bi-n clusters, respectively. Very similar centers are present in Bi- and Pb-doped oxide and chalcogenide glasses. Bi-implanted and Bi melt-doped chalcogenide glasses display new PL bands, indicating that new Bi centers are formed. Bi-related PL bands have been observed in glasses with very similar compositions to those in which carrier-type reversal has been observed, indicating that these phenomena are related to the same Bi centers, which we suggest are interstitial Bi2+ and Bi clusters. (c) 2013 Optical Society of America
Analogie mezi fotoluminescencí a změnou typu vodivosti v Bi- a Pb-dotovaných sklech
Keywords: germanium oxide glasses; amorphous-semiconductor diodes; band infrared luminescence; chalcogenide glasses; optical-properties; fiber laser; bismuth; emission; lead; amplification; germaničitá skla, amorfní polovodivé diody, chalkogenidová skla, infračervená luminiscence, zesílení signálu, bismut, olovo, vláknové lasery